AVAIL Phosphorus Fertilizer Enhancer: Meta‐Analysis of 503 Field Evaluations. (1st January 2018) - Hopkins, Bryan G.; Fernelius, Kaitlynn J.; Hansen, Neil C.; Eggett, Dennis L.
Abstract : Core Ideas: Meta‐analysis shows a significant yield increase of 2.1% with AVAIL+P fertilizer. Many AVAIL studies were not conducted under P responsive conditions. Likelihood of response increases with low soil test P and P rate and extreme pH. Average yield response increases to 4.6% when only likely to respond sites included. Enhanced efficiency fertilizer should be evaluated under P responsive conditions. AVAIL, a maleic‐itaconic copolymer acid marketed to enhance P fertilizers, has been studied on a variety of crop species. Data from all known field studies comparing P fertilization with and without AVAIL was amassed into a meta‐analysis of 503 field observations. The average yield increase was a modest, although statistically significant, 2.1% ( P < 0.0001). However, only 116 of these observations were conducted under conditions where a positive yield response to a P enhancement product would be expected– that is, low soil test phosphorus (STP), strong alkaline or acid pH, and low P fertilizer rate. As such, the data was parsed into a subset of only those observations that were evaluated under responsive conditions, resulting in a greater magnitude of a yield response to AVAIL at 4.6% ( P < 0.0001). Further parsing of the data, by eliminating any data not published in refereed or thesis/dissertation sources resulted in an average increase of 5.8% ( P = 0.0039). AVAIL effectively increased yields when used appropriately under conditions where a P response was expected. Testing enhanced efficiency fertilizer products in a variety of conditions is useful, but the conclusions from the multitude of studies with AVAIL in environments where no response to P fertilizer enhancement product would be expected may lead to erroneous conclusions if the data is not further parsed and categorized. These data demonstrate the importance of applying fundamental soil fertility principles when designing and evaluating fertilizer crop response studies.